اثر البرامج التدريبية الرياضية على الاداء الميداني لاعوان الحماية المدنية - مسكين عبد الله/بطاهر صارة (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
اﺳﺘﻬﺪﻓﺖ اﻟﺪراﺳﺔ إﱃ اﻟﺘﻌﺮف ﻋﻠﻰ ﻧﻮﻋﻴﺔ اﻟﻌﻼﻗﺔ ﺑﲔ اﻟﱪاﻣﺞ اﻟﺘﺪرﻳﺒﻴﺔ اﻟﺮﻳﺎﺿﻴﺔ و اﻷداء اﳌﻴﺪاﱐ ﻟﺪى أﻓﺮاد اﳊﻤﺎﻳﺔ اﳌﺪﻧﻴﺔ ﺑﻮﻻﻳﱵ ﻣﺴﺘﻐﺎﱎ و ﺗﻴﺎرت اﻧﻄﻼﻗﺎ ﻣﻦ اﻹﺷﻜﺎﻟﻴﺔ " ﻣﺎ ﻫﻮ ﺗﺄﺛﲑ اﻟﱪاﻣﺞ اﻟﺘﺪرﻳﺒﻴﺔ اﻟﺮﻳﺎﺿﻴﺔ ﻋﻠﻰ ﲢﺴﲔ اﻷداء اﳌﻴﺪاﱐ ﻷﻋﻮان اﳊﻤﺎﻳﺔ اﳌﺪﻧﻴﺔ " وﻗﻤﻨﺎ ﺑﻮﺿﻊ ﻓﺮﺿﻴﺔ ﻋﺎﻣﺔ ﻣﻔﺎدﻫﺎ أن اﻟﱪاﻣﺞ اﻟﺘﺪرﻳﺒﻴﺔ اﻟﺮﻳﺎﺿﻴﺔ ﺗﺴﺎﻫﻢ ﰲ ﲢﺴﲔ اﻟﻠﻴﺎﻗﺔ اﻟﺒﺪﻧﻴﺔ و اﳉﺎﻧﺐ اﻟﻨﻔﺴﻲ و اﻟﺬﻫﲏ ﻷﻋﻮان اﳊﻤﺎﻳﺔ اﳌﺪﻧﻴﺔ ﳑﺎ ﻳﻨﻌﻜﺲ إﳚﺎﺑﺎ ﻋﻠﻰ ﻣﺮدودﻫﻢ أﺛﻨﺎء اﳋﺪﻣﺔ، و ﻗﺪ ﴰﻠﺖ اﻟﻌﻴﻨﺔ ﻋﻠﻰ 209 ﻋﻮن ﰎ اﺧﺘﻴﺎرﻫﻢ ﺑﻄﺮﻳﻘﺔ ﻋﺸﻮاﺋﻴﺔ ﻣﻦ و ﺣﺪﺗﲔ رﺋﻴﺴﻴﺘﲔ ﻟﻠﺤﻤﺎﻳﺔ اﳌﺪﻧﻴﺔ ﻟﻮﻻﻳﱵ ﻣﺴﺘﻐﺎﱎ و ﺗﻴﺎرت و ﻣﻦ ﺧﻼل ﻫﺬا اﻧﺘﻬﺞ اﻟﺒﺎﺣﺜﺎن ﰲ دراﺳﺘﻬﻤﺎ اﳌﻨﻬﺞ اﻟﻮﺻﻔﻲ و ﰎ اﻹﻋﺘﻤﺎد ﻋﻠﻰ أداة اﻻﺳﺘﺒﻴﺎن و اﳌﺘﻤﺜﻠﺔ ﰲ اﺳﺘﻤﺎرة اﺳﺘﺒﻴﺎن ﻣﻜﻮﻧﺔ ﻣﻦ 4 ﳏﺎور اﻟﱵ ﲢﺘﻮي ﻋﻠﻰ 34 ﺳﺆال و ﻗﺪ ﰎ ﺗﻄﺒﻴﻖ اﻷﺳﺎﻟﻴﺐ اﻹﺣﺼﺎﺋﻴﺔ اﳌﻨﺎﺳﺒﺔ ﻟﺘﺤﻠﻴﻞ اﻟﻨﺘﺎﺋﺞ و ﺗﻔﺴﲑﻫﺎ و اﻟﱵ ﻣﻨﻬﺎ اﻟﻨﺴﺐ اﳌﺌﻮﻳﺔ، اﺧﺘﺒﺎر اﳌﺮﺑﻊ ﻛﺎ ، ² ﻣﺴﺘﻮى اﻟﺪﻻﻟﺔ، و درﺟﺔ اﳊﺮﻳﺔ، و ﺑﺎﻟﺘﺎﱄ أﻇﻬﺮت ﻧﺘﺎﺋﺞ اﻟﺪراﺳﺔ ﻋﻦ وﺟﻮد ﻋﻼﻗﺔ إﳚﺎﺑﻴﺔ ذات دﻻﻟﺔ إﺣﺼﺎﺋﻴﺔ ﺑﲔ اﻟﱪاﻣﺞ اﻟﺘﺪرﻳﺒﻴﺔ اﻟﺮﻳﺎﺿﻴﺔ و اﻷداء اﳌﻴﺪاﱐ ﻟﺪى أﻋﻮان اﳊﻤﺎﻳﺔ اﳌﺪﻧﻴﺔ، و ﰎ اﻟﺘﺄﻛﻴﺪ ﻋﻠﻰ ﺗﺄﺛﲑ اﻟﱪاﻣﺞ اﻟﺘﺪرﻳﺒﻴﺔ اﻟﺮﻳﺎﺿﻴﺔ ﻋﻠﻰ اﻷداء اﳌﻴﺪاﱐ و أﺛﺮﻩ ﻋﻠﻰ ﻣﺴﺘﻮى اﻟﺘﺪﺧﻼت اﳌﻴﺪاﻧﻴﺔ ﻷﻓﺮاد اﳊﻤﺎﻳﺔ اﳌﺪﻧﻴﺔ و دورﻩ ﰲ ﲢﺴﲔ أداء ورﻓﻊ ﻣﻦ ﻣﺮدودﻳﺘﻬﻢ . و ﻣﻦ ﺟﻬﺔ أﺧﺮى ﻳﻜﺴﺐ اﻷﻋﻮان اﻟﻠﻴﺎﻗﺔ اﻟﺒﺪﻧﻴﺔ اﻟﱵ ﺗﻌﺘﱪ أﻫﻢ ﻋﻨﺼﺮ واﺟﺐ ﺗﻮﻓﺮﻩ ﰲ اﻷﻋﻮان و اﻟﱵ ﺗﺴﺎﻫﻢ ﰲ ﻗﺴﻂ ﻛﺒﲑ ﰲ ﺗﻄﻮﻳﺮ أداﺋﻬﻢ و ﺗﺰﻳﺪ ﻣﻦ ﻛﻔﺎء ﻢ، وﰲ اﻷﺧﲑ ﻳﻮﺻﻲ اﻟﺒﺎﺣﺜﺎن ﺑﻀﺮورة ﺗﻮﻓﲑ اﳌﻨﺸﺎت و اﳌﺮاﻓﻖ اﻟﺮﻳﺎﺿﻴﺔ و ذﻟﻚ ﺣﱴ ﻳﺘﺴﲎ ﻷﻋﻮان اﳊﻤﺎﻳﺔ اﳌﺪﻧﻴﺔ ﻣﻦ ﳑﺎرﺳﺔ اﻟﺮﻳﺎﺿﺔ و اﻟﺘﺪرﻳﺐ اﻟﺪاﺋﻢ و اﳌﺴﺘﻤﺮ ﻟﻠﻤﺤﺎﻓﻈﺔ ﻋﻠﻰ اﻟﻠﻴﺎﻗﺔ اﻟﺒﺪﻧﻴﺔ و اﻛﺘﺴﺎب اﳌﻬﺎرات اﳊﺮﻛﻴﺔ و اﻟﺒﺪﻧﻴﺔ و اﻟﻔﻜﺮﻳﺔ اﻟﱵ ﺗﺴﺎﻋﺪ اﻟﻌﻮن ﰲ ﺗﺪﺧﻼﺗﻪ . // // // // // / The study aimed to identify the nature of the relationship between sports training programs and field exercices among civil protection agents in the wilayas of Mostaganem and Tiaret. Based on the question: "What is the impact of sports training programs on improving the field performance of civil protection agents?" A general hypothesis was posed, that training programs in sports contribute to improving physical , psychological, and mental aspects for civil protection agents, which positively reflects on their performance during various interventions. The sample included 209 agents were selected, randomly from two main units for civil protection in the wilayas of Mostaganem and Tiaret. This approach followed the descriptive method and relied on the descriptive and analytical tool through a questionnaire consisting of 4axes containing 34 questions. Appropriate statistical methods were applied to analyse the results and interpret them, including the percentages, the 2k level of significance, and the degrees of freedom. The study results showed a positive and statistically significant correlation between training programs and job performance of civil protection agents. The correlation was verified regarding the impact of sports training programs on physical readiness and its role in improving performance and reducing effort. Agents acquired physical and psychological skills that contributed to improving their performance during intervention.The study recommende adopting a unified training method for agentd and using the study tool as a measure of physical and mental readiness, with the researchers proposing a model training program and guiding strategy. The researchers recommend the necessity to providing facilities and equipment to enable civil protection agents to practice sports and undergo continuous and ongoing training. This is to help maintain physical fitness and acquire physical, motor, and cognitive skills that assist the agent in performing their duties effectively.
LES-2025-5
Keywords: اﻟﱪاﻣﺞ اﻟﺘﺪرﻳﺒﻴﺔ اﻟﺮﻳﺎﺿﻴﺔ; ، أﻋﻮان اﳊﻤﺎﻳﺔ اﳌﺪﻧﻴﺔ; اﻷداء اﳌﻴﺪاﱐ: Sports Training Programs; physical Performance; Civil Protection Agents